NIEKTÓRE ASPEKTY PRAWNE REFORMY SYSTEMU EMERYTALNEGO - Piotrowski, Włodzimierz (Wydział Prawa i Administracji UAM, 1999)
The article relates to legal issues involved with the realisation of the mentioned reform, in force in Poland from January 1st, 1999, which fundamentally changes the system of social insurance in Poland. The kind o f social insurance comprising the whole of employees and a majority of non-employed population groups which has been realised up to the present by the State on the basis of redistribution principle and the so-called „generations agreement” - is now being replaced, for the people under 30, with additional insurance which is based on capital principle and has a form of an obligatory savings system for the pension purpose within the framework of some open pension founds called the second pillar, completed also with voluntary savings in the so-called employees’ founds which are also called the third pillar o f the system of social insurance. The Author found questionable giving the name of social insurance to the additional insurance based on capital principle and, next, also - including in this system the State officers who up to the present have profited o f social provision, as well as, finally, differenciation of the principles for social insurance after the criterion of the age. In the Authors’ opinion the aim of the recent reform could be reached on the way of giving back the authentically assurance character to the new social insurance. Obligatory saving in private pension founds diminishes seriously the income of the Found o f Social Insurance System but, for young generation, it does not assure in the same time ćmy insurance for the old age, because the State does no longer guarantee the solvency o f pension performances in the future. 29 Takim
CHOSEN LEGAL ASPECTS OF THE REFORM OF PENSIONS FOR THE RETIRED